Quo vadis? Inequality and poverty dynamics across Russian regions - Ruslan Yemtsov (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2003)
This paper analyses regional data on inequality and poverty in Russia during 1994-2000 using published series from the regionally representative Household Budget Survey. The paper finds that the share of inequality in Russia coming from the between-regions component is large (close to a third of the total inequality), growing, and accounts for most of the increase in national inequality over 1994-2000. The paper demonstrates an absence of interregional convergence in incomes across Russian regions using various techniques. On the other hand, the paper finds evidence of convergence in inequality within regions, trended towards an internationally high level. Based on these two findings, the paper projects dynamics of inequality and poverty in Russia over a ten-year time horizon. The projections show that if the observed trend continues, by 2010 the absolute majority of Russia's poor will be concentrated in a few permanently impoverished regions, while relatively more affluent regions will become virtually free of poverty. Finally, the paper relates fluctuations in inequality within regions to a set of factors classified into four broad categories: endowments and initial conditions, preferences, policies, and shocks. Among these factors short-run fluctuations of the unemployment rate are revealed as significant and strong signals of inequality.
Keywords: C13; C15; D31; P29; P27; R12; R23; R29; 330; Russia; transition; inequality; poverty; regional economics; convergence; Regionale Einkommensverteilung; Armut; Räumliche Verteilung; Entwicklungskonvergenz; Russland